2018
DOI: 10.2217/fmb-2017-0168
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Hypoxia-Inducible Factor 1 α in Experimental Pulmonary Tuberculosis: Its Implication as a New Therapeutic Target

Abstract: HIF-1α has a dual role in experimental TB. This finding could have therapeutic implications because combined treatment with 2-methoxyestradiol and antibiotics appeared to eliminate mycobacteria more efficiently than conventional chemotherapy during advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 39 publications
0
27
0
1
Order By: Relevance
“…This is followed by a later adaptation/resolution phase (24–48 h post-infection) in which there is a down regulation of immune response genes and a transition from glycolysis to mitochondrial oxidation in mouse BMDMs. Another study using a mouse model of progressive pulmonary tuberculosis, also demonstrated that the Mtb H37Rv infection is divided into two phases (Baay-Guzman et al, 2018 ). During the first phase, corresponding to the first month, granulomas are produced.…”
Section: Macrophage Response To Mtb Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is followed by a later adaptation/resolution phase (24–48 h post-infection) in which there is a down regulation of immune response genes and a transition from glycolysis to mitochondrial oxidation in mouse BMDMs. Another study using a mouse model of progressive pulmonary tuberculosis, also demonstrated that the Mtb H37Rv infection is divided into two phases (Baay-Guzman et al, 2018 ). During the first phase, corresponding to the first month, granulomas are produced.…”
Section: Macrophage Response To Mtb Infectionmentioning
confidence: 99%
“…When a potential HDT, 2-methoxyestradiol that inhibits HIF-1α, was administered during the first phase, the lung bacillary loads were greater than the control group, and a greater area of the lung surface was affected by pneumonia. But when 2-methoxyestradiol was administered in the second phase, both the lung bacillary load and lung surface area affected by pneumonia were significantly reduced (Baay-Guzman et al, 2018 ). However, it is not known if this biphasic response is exhibited in infected human macrophages.…”
Section: Macrophage Response To Mtb Infectionmentioning
confidence: 99%
“…Although not stressed by the authors, it is notable that these AM displayed a foamy phenotype unlike AM from WT mice (52), arguing that the uncontrolled activation of HIF-1α may contribute to FM formation. In line with this, it has recently been described that the activation of HIF-1α during late stages of infection with Mtb promotes the survival of infected FM (53), and that the activation of HIF-1α mediated by IFN-γ contributes to the formation of LBs in macrophages infected with Mtb (54). At least two hypotheses can explain how HIF-1α activation contributes to FM formation: 1) by suppressing FAO, and/or 2) by inducing endogenous fatty acid synthesis.…”
Section: Discussionmentioning
confidence: 65%
“…However, therapeutic stabilization of HIF1α has to be tailored individually. For instance, in a model of progressive pulmonary tuberculosis in BALB/c mice, the blockage of HIF1α worsened the disease during the early phase of infection, while it decreased bacterial load during late tuberculosis [212].…”
Section: Hif Stabilization As Therapeutic Strategy For the Control Ofmentioning
confidence: 99%